2007
DOI: 10.1111/j.1471-4159.2007.04755.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sphingosine kinase activity and mRNA in rodent brain

Abstract: Sphingosine-1-phosphate (S1P) is a lipid mediator that exerts multiple cellular functions through activation of a subfamily of G-protein-coupled receptors. Although there is evidence that S1P plays a role in the developing and adult CNS, little is known about the ability of brain parenchyma to synthesize this lipid. We have therefore analyzed the brain distribution of the enzymatic activity of the S1P synthesizing enzyme, sphingosine kinase (SPHK) [EC:2.7.1.91], as well as mRNA distribution for one of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 48 publications
7
80
1
Order By: Relevance
“…32 Ceramide can be further catabolized by ceramidases to generate sphingosine, which can be phosphorylated through the action of sphingosine kinase, generating S1P. 33 Sphingosine kinase activity in the brain was recently reported to increase 24 hours after ischemia in a mouse model of MCA occlusion 34 ; however, those increases were not necessarily the same as the S1P concentration in our study. As well, if elevation of sphingosine kinase activity accounts for the increase in S1P concentration after insult, the concentration of dihydro-S1P would increase because dihydrosphingosine is phosphorylated by sphingosine kinase isozymes to an extent similar to that of naturally occurring sphingosine.…”
Section: Discussioncontrasting
confidence: 55%
“…32 Ceramide can be further catabolized by ceramidases to generate sphingosine, which can be phosphorylated through the action of sphingosine kinase, generating S1P. 33 Sphingosine kinase activity in the brain was recently reported to increase 24 hours after ischemia in a mouse model of MCA occlusion 34 ; however, those increases were not necessarily the same as the S1P concentration in our study. As well, if elevation of sphingosine kinase activity accounts for the increase in S1P concentration after insult, the concentration of dihydro-S1P would increase because dihydrosphingosine is phosphorylated by sphingosine kinase isozymes to an extent similar to that of naturally occurring sphingosine.…”
Section: Discussioncontrasting
confidence: 55%
“…Unlike SphK1, high expression of SphK2 was observed mainly in adult kidney, liver, and brain, compared with other tissues (39,40). Recently, it was demonstrated that conjugated bile acids signal through the S1PR2 and activate SphK2 (11).…”
Section: S1p a Lipid Mediatormentioning
confidence: 99%
“…FTY720 is a structural analogue of sphingosine and has biological activity in vivo by being phosphorylated by SPHKs (Mandala et al 2002), which are abundantly expressed in the brain (Blondeau et al 2007;Bryan et al 2008). The phosphorylated form of FTY720 (FTY720P) activates S1PRs, mainly S1PR1, in a fashion similar to that of endogenous S1P.…”
Section: Introductionmentioning
confidence: 99%